Myocardial Recovery in Cardiogenic Shock - Kevin John; Adnan Khalif; Masaki Tsukashita; Manreet K. Kanwar (Methodist DeBakey Cardiovascular Journal)
The overarching goal of cardiogenic shock (CS) therapy is ensuring long-term survival. In recent years, increasing emphasis has been placed on analyzing mechanisms to improve outcomes in CS. This includes averting in-hospital mortality, modifying the disease process by promoting heart recovery while avoiding multiorgan failure, and circumventing complications related to both CS and treatment strategies deployed to treat CS. Heart replacement therapies represent a viable strategy for long-term survival but are restricted to a small, select percentage of patients. In this review we focus on pathophysiology of the shock state, with an emphasis on addressing reversible etiologies contributing to the decompensated state, optimizing physiological factors for recovery, and identifying therapeutic targets to promote recovery. We also review the known predictors of myocardial recovery, regardless of the etiology of CS. Lastly, we highlight the current gaps in knowledge in this field and support additional high-quality studies focusing on myocardial recovery in CS.